APPLICATION SPECIFIC PERFORMANCE ANALYSIS OF FRAME RELAY NETWORK USING PVCS - Khan, M. A. (The Nucleus, 2012)
Frame relay networks are incorporated in a Wide Area Network (WAN) to make communication possible across a large area. These networks use permanent virtual circuits (PVCs) to dedicate links for efficient communication by avoiding the repeated overhead of setup call. The PVCs use contract parameters such as Committed Information Rate (CIR), Committed Burst Size (BC) and Excess Burst Size (BE) to ensure specific standards of communication. With an application executing on a Frame Relay network, the PVCs affect the performance of the application depending upon the traffic passing through the network.In this paper, we analyze the performance of the Frame Relay network with respect to the applications executing on it. The PVCs are established in the network with high and low values of contract parameters (CIR, BC & BE). The throughput, network delay and delay variance are used as metrics for evaluating the performance of the network while executing FTP, Voice and Video applications. The experimentation results show that the increase in the values of the contract parameters reduces the delay for FTP application, whereas for the Voice application, the delay remains consistent. On the contrary, for the Video application, the network delay and delay variance increase with the increase in the values of the contract parameters. Furthermore, the throughput of the Frame Relay network increases for each application with the increase in the values of the contract parameters. With simultaneous execution of the three considered applications, the throughput, delay and delay variance increase with the increase in the values of contract parameters.